Hybrid in-situ and ex-situ hydrolysis of catalytic epoxidation neem oil via a peracid mechanism - Ismail Md. Rasib; Mohd Jumain Jalil; Nabisab Mujawar Mubarak; Intan Suhada Azmi (Scientific Reports)
Abstract The depletion of oil reserves and their price and availability volatility raise researchers’ concerns about renewable resources for epoxidized material. This study aims to produce in situ and ex-situ hydrolyzed dihydroxy stearic acid via the epoxidation of neem oil. Epoxidized neem oil was synthesized using in situ-generated performic acid. The Taguchi method was employed to optimize hydrolysis, aiming for maximum production of dihydroxystearic acid. The Taguchi method’s signal-to-noise (S/N) ratio analysis identified optimal conditions for producing dihydroxy stearic acid with a maximum hydroxyl value of 129.4 mg KOH/g: (1) water/neem oil molar ratio of 2:1, (2) water addition time of 90 min, and (3) reaction stop time of 120 min. ANOVA revealed the significant order of parameters as reaction stop time > water addition time > water/neem oil molar ratio. Lastly, a mathematical model was developed using MATLAB, applying the fourth-order Runge–Kutta method and simulated annealing optimization to determine the best-fitting kinetic model. This research aids in transforming neem oil into a value-added product, reduces petroleum dependence, and provides key insights into reaction kinetics for industrial applications.